A comparative study of black mulberry juice concentrates by thermal evaporation and osmotic distillation as influenced by storage. (December 2016) - Dincer, Cuneyt; Tontul, Ismail; Topuz, Ayhan
Abstract: In the present study, black mulberry juice was concentrated using thermal evaporation and osmotic distillation after clarification and pasteurization. The main quality parameters of the concentrates were comparatively investigated after reconstitution with different storage times and temperatures. The parameters investigated were: color, turbidity, pH, titratable acidity, anthocyanin content, percent polymeric color, antioxidant activity, 5-hydroxymethylfurfural (HMF) content and volatile profile. The anthocyanin content, volatile content and turbidity values of osmotically distillated samples were found to be higher than those of the thermal concentrates. Neither HMF nor furfural was detected in the samples soon after the processing; however, levels of process contaminants were found to increase gradually throughout the storage period in both concentrates. Thermal evaporation resulted in markedly higher HMF and furfural formation in comparison to the osmotic distillation process. The anthocyanin content and antioxidant activity of the concentrates decreased, whereas polymeric color ratio and turbidity values increased within longer storage time and higher storage temperature. Industrial relevance: Concentration is one of the key steps affects the chemical and physical properties of black mulberry juice since black mulberry phytochemicals, mainly anthocyanins, are labile to heat treatment and storage. Thermal evaporation has some drawbacks such as loss of fresh juice flavors, color degradation, reduction of nutritional value and formation of mutagenic compounds such as HMF and furfural. These drawbacks require alternative methods that involve minimal processing. Osmotic distillation can be recommended for black mulberry juice concentration in order to preserve its heat-sensitive components and to produce high-quality product. Highlights: Black mulberry juice was processed using thermal evaporation and osmotic distillation. Main quality parameters of the concentrates were comparatively investigated. HMF and furfural were not detected in concentrates after processing. Anthocyanin and volatile components in the samples decreased during storage. HMF and furfural increased gradually throughout the storage.